AN ANALYSIS OF TEXTBOOK “ENGLISH IN MIND: STUDENT’S BOOK STARTER” FOR THE 7TH YEAR STUDENTS OF JUNIOR HIGH SCHOOL BASED ON MERDEKA CURRICULUM - Encik Siti Adilah; Lalu Nurtaat; Udin; Ni Wayan Mira Susanti (Journal of English Education Forum (JEEF), 2023)
This research focuses on the analysis of a textbook intended for 7th-grade junior high school students, specifically designed according to the latest curriculum known as the Merdeka curriculum. The aim of this study was to determine the suitability of the textbook's content for 7th-grade students. The research followed a qualitative descriptive approach, utilizing content analysis as the methodology. The primary data source for this study was the English textbook "English in Mind: Student's Book Starter," published in 2010 by Cambridge University Press and authored by Herbert Puchta and Jeff Strank. The textbook analysis in this study considered eight criteria, namely: (1) goals and approach, including aims, objectives, teaching, and learning situations; (2) design and organization, encompassing the textbook package components and its overall organization; (3) language content, covering grammar and vocabulary; (4) skills, including listening, reading, speaking, and writing; (5) topics, which comprise subject content and social and cultural values; (6) methodology; (7) teacher's book; and (8) practical aspects. The findings of the study indicate that the textbook meets all eight criteria. Based on the analysis, the textbook was classified as being of satisfactory quality and suitable for use in 7th-grade junior high school.